Prevalence and determinants of eating disorder risk behaviours among adult women in Denmark: findings from nationwide cross-sectional health surveys between 2000 and 2023 - Heidi Amalie Rosendahl Jensen; Rikke Bjerring Plenborg; Michael Davidsen; Ola Ekholm; Lau Caspar Thygesen (Journal of Eating Disorders)
Abstract Background Eating disorders exhibit the highest mortality among mental disorders and are associated with serious physical and mental health symptoms. Short disease duration is a crucial predictor of recovery, and therefore, screening instruments targeting eating disorder risk behaviours are needed for preventive purposes. Furthermore, knowledge about potential determinants of such risk behaviours may refine future prevention strategies and initiatives. This study aimed to describe trends between 2000 and 2023 in the prevalence of eating disorder risk behaviours among adult women from the general population in Denmark and to explore associated determinants in 2023. Methods Data were derived from female respondents aged ≥ 16 years in the Danish Health and Morbidity Survey in 2000 (n = 1,704), 2005 (n = 2,709), and 2023 (n = 5,072), a nationwide cross-sectional health survey. Information on eating disorder risk behaviours was assessed by the validated screening instrument, Risk Behaviour for Eating Disorder 8-items (RiBED-8), and collected by self-administered questionnaires. The prevalence of eating disorder risk behaviours between 2000 and 2023 was described as proportions, whereas univariable and multivariable logistic regression models were used to explore potential associations between self-reported determinants and eating disorder risk behaviours in 2023. All analyses were stratified by age (16–24, 25–34, ≥ 35 years). Results The overall prevalence of eating disorder risk behaviours increased from 10.0% in 2000 to 20.6% in 2023 with the largest increase in age group 25–34 years (from 11.6 to 27.3%). In the adjusted regression models, higher levels of perceived stress were consistently associated with eating disorder risk behaviours across age groups (OR = 1.07–1.10). In contrast, the associations with low and high body mass index, current smoking, and loneliness varied across age groups. Conclusion Between 2000 and 2023, a two-fold increase in the overall prevalence of eating disorder risk behaviours was demonstrated among adult women in Denmark, which urgently calls for targeted prevention initiatives based on identified determinants. If left untreated, such risk behaviours may develop into clinical eating disorders with negative implications for society and individuals. Future studies are furthermore encouraged to examine eating disorder risk behaviour trends and determinants among men.